The Influence of Workload on Work Fatigue at the Musrem Bakeri Bread Shop at 3 Tembung Market - Isma Adawiah; Reni Agustina Harahap (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
An earlier survey of this study found that failure in the manufacture of bread was due to the work load in the work environment so it was aimed at knowing how the workload would affect the bakery fatigue. The method used in research is a quantitative that USES a sectional approach. The study is carried out at the musrem bakery located on market road 3. The population used in this study is all the workers at the musrem bakery. As for the sampling taken done with a total sampling technique. The study USES verification and containment tests with data collecting techniques through primary data as well as secondary data. As for the results of this study, p value of 0.162 with a value of more than 0.05, the test stated that there was no significant impact between the workload on the musrem bakery.